Pengaruh kenaikan tarif pajak pertambahan nilai pasca undang undang harmonisasi perpajakan terhadap kepatuhan pajak UMKM di Indonesia - Haryani, Umi; Susianti, Susianti (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2024)
UMKM in Indonesia are a medium-sized business sector that is able to support the country's economy. The enactment of the tax harmonization law(HPP) is the basis for the regulation of one of the UMKM. The implementation of the HPP Law, the Value Added Tax rate increased by 1%, which was originally 10% to 11% effective from April 1, 2022. Regulations related to PPN having an increase of 12% have been discussed and are planned to come into effect in 2025. This research method uses a qualitative literature review approach. Data sources are collected from various media sources both websites and journals. This study concludes that UMKM tax compliance has increased after the PPN rate increase. The increase in UMKM tax compliance is projected to increase Indonesia's overall tax revenue.